Numerical investigation of composite patch repair of inclined cracked panel using XFEM. (2021) - Makwana, Alpesh H.; Vyas, Nisarg; Barot, R.S.
Abstract: The life extension of the structure is an important area of research. Composite patch repair is widely used in restoring the strength of the cracked structures. Effective repair should offer repair efficiency as well as repair durability. The crack exists in the structure usually involves mixed-mode loading condition and therefore the study of the panel with inclined crack is significant. This article aims to investigate the performance of the inclined cracked panel bonded with composite patch. Numerical analysis of inclined cracked panel is carried out in ABAQUS. The J-integral and interfacial stresses are investigated which confirms repair efficiency and durability respectively. The orientation of the material in the composite influences the amount of reinforcement applied to the cracked panel and hence the effect of different material orientations is evaluated. The effect of patch stiffness on J-integral and interfacial stresses is also investigated. The results obtained indicate that the patch with adequate stiffness can contribute to diminish the J-integral and interfacial stresses to enhance the performance.